The features of Tat protein of human immunodeficiency virus type 1 (Retroviridae: Lentivirus: Lentivirus humimdef1) non-A6 variants, characteristic for the Russian Federation - Anna I. Kuznetsova; Anastasiia A. Antonova; Aleksey V. Lebedev; Ekaterina N. Ozhmegova; Anastasia V. Shlykova; Ilya A. Lapovok; Oxana V. Galzitskaya (Вопросы вирусологии)
Introduction. Tat protein is a trans-activator of HIV-1 genome transcription, with additional functions including the ability to induce the chronic inflammatory process. Natural amino acid polymorphisms in Tat may affect its functional properties and the course of HIV infection.